Statecraft, Witchcraft, God’s Craft: Religious Diversity and the Forces of Law in South Africa - Burchardt, Marian (Journal of religion in Africa, 2017)
Legal anthropologists and sociologists of religion increasingly recognize the importance of law in current controversies over religious diversity. Drawing on the case of South Africa, this article explores how such controversies are shaped by contestations over what counts as ‘religion’. Analyzing the historical context and emergent forms of institutional secularity from which contemporary contestations over religious diversity draw, the article explores debates and practices of classification around religion, tradition, and culture, and the ways in which these domains are co-constituted through their claims on the law: on the one hand through an analysis of religion-related jurisprudence; on the other hand through an examination of the debates on witchcraft, law, and religion. I argue that the production of judicial knowledge of ‘religion’, ‘culture’, and ‘tradition’ is tied up with contestations over the power to define the meaning of the domains. In fact, contrary to notions of constitutionality in which rights seem to exist prior to the claims made on their basis, in a fundamental sense rights struggles help to constitute the contemporary human rights dispensation. Against the Comaroffs’ claim that judicialization depoliticizes power struggles, I show that legal claims making remains vibrantly political.